Toward an integrated Arctic observing network (National Academies Press, 2006)
Observable changes with regional and global implications, such as warming temperatures and reduced sea ice, are taking place across the Arctic. However, the record of Arctic observations suffers from incomplete geographic coverage and limited duration, and measurements are not well coordinated. This makes it difficult to comprehensively describe current conditions in the Arctic, let alone understand the changes that are underway or their connections to the rest of the Earth system. The U.S. National Science Foundation asked for guidance to help design a pan-arctic observing network. This book outlines the potential scope, composition, and implementation strategy for an arctic observing network. Such an integrated, complete, and multidisciplinary environmental observing network will improve society's understanding of and ability to respond to ongoing systemic changes in the Arctic and its capability to anticipate, predict, and respond to future change both in the Arctic and around the globe. The network would build on and enhance existing national and international efforts and deliver easily accessible, complete, reliable, timely, long-term, pan-arctic observations. Because many potential components of the network already exist or are being planned, and because of the surge of activity during the International Polar Year, there is an immediate opportunity for major progress.